2017
DOI: 10.1039/c7en00240h
|View full text |Cite
|
Sign up to set email alerts
|

The double influence mechanism of pH on arsenic removal by nano zero valent iron: electrostatic interactions and the corrosion of Fe0

Abstract: The pH has a significant impact on arsenic (As) removal by nano zero valent iron (nZVI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Removal of As(V) and As(III) by nZVI has been widely documented [28][29][30][31][32][33][34][35][36][37][38][39]. Therefore, confirming the solution chemistry or removal efficiency of nZVI for As(V) separation is not an objective of this work.…”
Section: Solution Chemistry Of As(v) and Nzvi Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Removal of As(V) and As(III) by nZVI has been widely documented [28][29][30][31][32][33][34][35][36][37][38][39]. Therefore, confirming the solution chemistry or removal efficiency of nZVI for As(V) separation is not an objective of this work.…”
Section: Solution Chemistry Of As(v) and Nzvi Reactionsmentioning
confidence: 95%
“…Arsenic pollution is a global problem, and its cost-effective and reliable removal is frequently a challenge for environmental scientists and engineers [16,17]. nZVI is an effective nano-agent for As(V) and As(III) sequestration [16,17,[30][31][32][33][34][35][36][37][38][39]. Although changes in the arsenic valence state have been observed during nZVI treatment, arsenic speciation and underlying mechanisms are not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum adsorption capacity for As(III) and As(V) at pH 6.5 calculated from Langmuir model was 18.2 and 12.0 mg g À1 , respectively. 109 Wu et al 110 investigated the double inuence mechanism of pH on arsenic removal by nZVI (with an average particle size varying from 30 to 50 nm). The results indicated that an increasing pH decreased the g-FeOOH and increased the Fe 3 O 4 /g-Fe 2 O 3 content in the corrosion products of nZVI, thus enhancing the adsorption affinity of nZVI to As(V).…”
Section: Nanoscale Zero-valent Iron (Nzvi) and Nzvi Supported Adsorbentsmentioning
confidence: 99%
“…An increase in groundwater pH ( Figure 3A ) has been reported to affect transport, mobility and adsorption of contaminants ( Zhang and Elliott, 2006 ), including impairment of the removal of both species of arsenic due to electrostatic repulsion ( Park et al, 2009 ). However, a significant effect of the nanoparticles on the adsorption of As(V) in the groundwater of Nitrastur is unlikely since the highest pH value reached was well below the values that induce a marked decrease of nZVI surface potential and would therefore greatly hinder the adsorption of this form of arsenic ( Park et al, 2009 ; Wu C. et al, 2017 ). On the other hand, an increase in the pH of groundwater alters the proportion of corrosion products of nZVI, such as maghemite, which has a higher adsorption affinity toward As(V) ( Wu C. et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%